Trends in population-based incidence, diagnostics, and mortality of acute superior mesenteric artery occlusion - Soltanzadeh-Naderi, Y.; Acosta, S. (Frontiers in Surgery, 2024)
Acute occlusion of the superior mesenteric artery (SMA) results in lethal intestinal ischemia. Results from two previous population-based studies in Malmö, Sweden, suggest a decreasing incidence of acute SMA occlusion. This study aimed to evaluate trends in the epidemiology of acute SMA occlusion in Malmö. The report was a retrospective population-based study conducted from 2014 to 2019 on patients with acute SMA occlusion residing in Malmö municipality. Patient data were retrieved from Skåne University Hospital and postmortem examinations. Epidemiological data were compared to those of the two earlier studies, in particular to the one conducted from 2000 to 2006. Sixteen patients with acute SMA occlusion resided in Malmö municipality. The incidence of acute SMA occlusion significantly decreased from 5.4/100,000 person-years to 0.8/100,000 person-years. The ratio of acute SMA occlusion to non-occlusive mesenteric ischemia (NOMI) decreased from 12.5:1 to 0.9:1 (p < 0.0001), the proportion of inhabitants aged 80 years or above in the population decreased from 6.0% to 4.3% (p < 0.0001), and the autopsy rate decreased from 25% to 14% (p < 0.0001). The in-hospital mortality rate decreased from 63% to 44% (p = 0.14). The incidence of acute SMA occlusion seems to have decreased significantly in Malmö, probably due to high-resolution computed tomography angiographies being available around the clock to distinguish acute SMA occlusion from NOMI, a reduced proportion of elderly individuals, improved control of medical risk factors, and a decrease in autopsy rates.